ANALISIS FINANCIAL DISTRESS DENGAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Cristyn Yohanna Sianipar; Netty Herawaty; Rahayu Rahayu (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This research aims to analyze the effect of the Altman Z-score financial ratio on financial distress in automotive and component manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The independent variables in this study include Net Working Capital to Total Assets, Retained Earnings to Total Assets, Earning Before Interest, and Tax to Total Assets dan Book Value of Equity to Total Liabilities. The dependent variable is financial distress. Purposive sampling was used to select a sample of 12 companies, and descriptive statistics were applied using the SPSS version 25 program. The results of the study indicate that 7 companies are healthy, 3 companies are experiencing financial distress, and 2 companies are in a gray area. The result found that all four financial ratios partially have an effect on financial distress and simultaneously all four ratios also have an effect on financial distress.